Hardiness personality and mental health of financially-struggling medical students in private universities in China: the intervening roles of coping styles and gender - Liu, Huan; Chen, Jiabao; Peng, Qinghe; Zhang, Hao; He, Yating (Frontiers in Public Health, 2024)
BackgroundChinese adolescents are at higher risk of depression, especially the mental health problems of financially disadvantaged medical students, which are significantly higher than those in other age groups, which brings great challenges to the mental health workers in universities.Methods1,280 medical students with a family poverty background in China completed a questionnaire on hardiness personality, coping style and mental health. After descriptive statistics and Pearson correlation analysis between hardiness personality, coping style and mental health levels, we tested the mediation of coping style and the moderating effects of gender.ResultsHardiness personality significantly positively affected the financially-struggling medical student’s mental health level. Positive coping style had a significant positive impact on hardiness personality and mental health level, while negative coping style had a significant negative effect on mental health level. Positive coping and negative coping are the mediators between financially-struggling medical students’ hardy personalities and mental health levels. In medical students with a family poverty background, gender plays a regulatory role in coping style and mental health levels. In medical students with a family poverty background, gender plays a moderate role in coping style and mental health levels.ConclusionThis study adds some knowledge about the effects of hardiness personality on individual mental health. It makes new recommendations for improving the mental health status of vulnerable groups, while it can support future investigations by scholars and educators on how to improve the mental health of students under learning and financial-related stress.